Conglomerate Mergers as Defense Against the Risk of Relative Price Variability - Ahtiala, Pekka (The Review of Economics and Statistics, 2000)
This paper studies the effects of the risk of relative price variability on the optimal structure of a firm's cash flows with an application of portfolio theory. It is suggested that, when relative price risk is greater, it is optimal for the management to diversify, at the margin, and emphasize economies of scale or scope when the risk is smaller. Conglomerate mergers should therefore be positively associated with relative price risk, given the variables affecting mergers as a whole. Empirical evidence is found to lend support to the theory. The inflation rate explains conglomerate mergers even better, which suggests that relative price risk may constitute another real resource cost of inflation.